Thecla, een beeld van een vrouw - Misset- van de Weg, Magdalena Wilhelmina (Proeven van vrouwenstudies theologie ; deel V, 1999)
In her article 'Thecla, the Image of a Woman' Magda Misset-van de Weg shows how the Second Century story of a young woman from Iconium illuminates a common experience for religiously inspired women, namely the mistrust, doubt and lack of appreciation of contemporaries. Thecla, as an itinerant woman preacher who rejected the cultural norms in favour of Christianity, not only experienced the disapproval of her family and society but also was regarded with suspicion by the Christian leadership including Paul. Nevertheless the Acts of Thecla also bears witness to the overcoming of this resistance through the active encouragement and effort of female supporters. We are offered an image of a community where women not only survive whole but also take divinely inspired initiatives.